2016
DOI: 10.1093/ntr/ntw164
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Exposure to Harmful and Potentially Harmful Smoke Constituents With the Tobacco Heating System 2.1

Abstract: Introduction:Heating rather than burning tobacco reduces levels of harmful and potentially harmful constituents, and consumer products using this approach aim to reduce exposure to tobacco toxicants. The Tobacco Heating System (THS) version 2.1 has been enhanced from earlier prototypes with an improved heat control and sensorial experience and thereby user acceptance. Exposure measurements are required to determine whether it may be possible to reduce the individual health risk compared to smoking combustible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…The use of IQOS or glo reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use [74,75]. After switching from conventional cigarettes to HTPs (IQOS or glo), a significant reduction in the levels of biomarkers of exposure to harmful and potentially harmful constituents was observed [76][77][78].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 96%
See 1 more Smart Citation
“…The use of IQOS or glo reduced the exposure to smoke toxicants in a manner comparable to quitting tobacco use [74,75]. After switching from conventional cigarettes to HTPs (IQOS or glo), a significant reduction in the levels of biomarkers of exposure to harmful and potentially harmful constituents was observed [76][77][78].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 96%
“…The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78]. However, there have been no independent studies regarding short-term and longterm health consequences of HTP use.…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…A World Health Organization (WHO) report on HTPs highlighted that HTP marketing acknowledges the health risks of traditional cigarettes and indicates that HTPs are “cleaner,” “reduced-risk” products ( WHO, 2018 ). Initially, most published research regarding iQOS were funded by PMI and its affiliates ( Glantz, 2018a ), indicating lower harmful tobacco carcinogen levels ( Brossard et al, 2017 ; Jaccard et al, 2017 ; Ludicke et al, 2017 , 2018 ; Martin Leroy et al, 2012 ; Pratte et al, 2017 ; Roethig et al, 2005 , 2007 ). However, independent analyses of PMI’s research ( Glantz, 2018a ) elucidated that (a) PMI’s list of 58 harmful and potentially harmful constituents was lower in iQOS emissions compared with cigarette smoke ( St. Helen et al, 2018 ); (b) PMI only reported on 40 of 93 constituents on the FDA’s list for iQOS ( St. Helen et al, 2018 ); (c) 56 other constituents not included on either list were higher in iQOS emissions ( St. Helen et al, 2018 ); (d) iQOS and conventional cigarettes showed no difference in most biomarkers of potential harm ( Glantz, 2018b ); and (e) iQOS has possible hepatotoxicity and potential for unexpected organ toxicity not previously associated with cigarettes ( Chun et al, 2018 ).…”
Section: Heated Tobacco Productsmentioning
confidence: 99%
“…By heating instead of burning tobacco, THS avoids or reduces the formation of many toxic combustion products. Clinical studies have shown favorable biological effects in smokers who switched from cigarette to different non-combusted products [ 4 6 ]. While this makes risk reduction at the individual level possible, a population health benefit additionally depends on smokers actually switching from cigarettes to THS.…”
Section: Introductionmentioning
confidence: 99%